Recent advances in financial engineering 2012 :bproceedings of the International Workshop on Finance2012, the University of Tokyo, Japan, 30-31 October 2012 / ceditors Akihiko Takahashi, The University of Tokyo,Japan, Yukio Muromachi, Tokyo Metropolitan University,Japan,Takashi Shibata,Tokyo Metropolitan University,Japan - Takahashi, Akihiko; Muromachi, Yukio; Shibata, Takashi (World Scientific, 2014)
Recent Advances in Financial Engineering 2012 is the .Proceedings of the International Workshop on Finance 2012, held in Kyoto, in Autumn 2012 with the aim of exchanging new ideas in financial engineering among researchers from various countries from both academia and industry.The workshop was held as a successor to the Daiwa International Workshop (2004-2008), the KIER-TMU International Workshop (2009-2010) and the International Workshop on Finance (2011).This workshop was organized by the Center for Advanced Research in Finance (CARF), Graduate School of Economics, the University of Tokyo, and Graduate School of Social Sciences, TokyoMetropolitan University. This book serves as a bridge between academic researchers and practitioners. It contains fifteen papers, all refereed, representing the presentations at the workshop. The papers address state-of-the-art techniques in financial engineering.